LEADERSHIP PROFILE OF LAWYER CANDIDATES IN KAZAKHSTAN - Lukashova, Svetlana; Gumarova, Nazgul (PUPIL: International Journal of Teaching, Education and Learning, 2017)
There is a perception that lawyers differ from other professionals in a variety of ways. If ‘lawyer personality’ exists, we will attempt to explore the personality profile of Kazakhstani law students and predict their leadership skills. Understanding their strengths and weaknesses is an essential part of self-knowledge for leaders. The study examines the influence of 1) physiological (temperament and behavioral activation / inhibition system), 2) cognitive (brain dominance and intelligence), 3) personality (Myers-Briggs Type Indicator and locus of control), and 4) morality (career values) factors on the development of leadership capacity of future lawyers. To investigate this issue in Kazakhstani educational environment we surveyed 150 students of Law Department from Suleyman Demirel University. The results demonstrated the evidence of the impact of law students’ personality on leadership capacity: they are transactional leaders, decisive and responsible, making others readily follow them and get the job done. Hopefully, the preferences that the students demonstrated in interpersonal /intrapersonal intelligence and their desire to satisfy their status , service, and social relationship needs in law career will facilitate their move from narcissistic transactional towards success for transformational servant leadership style.